Mathematical Model of Linear Switched Reluctance Motor with Mutual Inductance Consideration - Nikolay Grebennikov; Alexander Kireev; Nikolay Kozhemyaka (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
This paper presents developing an mathematical model for linear switched reluctance motor (LSRM) with account of the mutual inductance between the phases. Mutual interaction between the phases of LSRM gives the positive effect, as a rule the power of the machine is increased by 5-15%.